Analisis Rasio Keuangan Untuk Menilai Kinerja Keuangan Pada PT Unilever Indonesia Tbk Periode 2021 – 2023 - Oktavia, Kharisma; Pudyaningsih, Agnes Ratna; Oktafiah, Yufenti (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
The purpose of this research is to assess the financial performance of PT. Unilever Indonesia Tbk during the 2021 - 2023 period based on liquidity, solvency, activity and profitability ratios. The population of this research is the annual financial report of PT Unilever Indonesia Tbk for the period 2021 - 2023. The sampling technique uses a non-probability sampling method with a saturated sampling approach, namely the financial report of PT Unilever Indonesia Tbk which includes the Balance Sheet and Profit and Loss Report for 2021 - 2023. This research is quantitative with a comparative analysis method using the Year-to-year Changes Analysis. The research results show that in terms of liquidity and solvency ratios the performance is less than optimal because cash and cash equivalents have not been able to fulfill all their obligations. The activity ratio performs well in managing accounts receivable turnover, inventory and asset turnover even though the company's working capital turnover is less than optimal. From the profitability aspect, the company is able to generate profits and use assets efficiently based on GPM, NPM and ROA indicators. However, the ROE ratio shows poor performance, along with the high DER ratio which indicates the company's dependence on debt.